2019
DOI: 10.3390/agronomy9070384
|View full text |Cite
|
Sign up to set email alerts
|

Charcoal Fine Residues Effects on Soil Organic Matter Humic Substances, Composition, and Biodegradability

Abstract: Biochar has been shown as a potential mean to enhance carbon sequestration in the soil. In Brazil, approximately 15% of the produced charcoal is discarded as charcoal fines, which are chemically similar to biochar. Therefore, we aimed to test charcoal fines as a strategy to increase soil carbon sequestration. Charcoal fines of hardwood Mimosa scabrella were incorporated into a Cambisol down to 10 cm (T1 = 0 and T4 = 40 Mg ha−1) in Southern Brazil. Soil samples were collected (0–30 cm) 20 months after charcoal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
1
3
1
Order By: Relevance
“…The lower proportion of aromatic groups in our study compared to other soils subjected to annual burning Leal et al 2019), is possibly due to the enhanced decomposition of aromatic groups by soil micribiota in the hot and humid climate of the region . The high percentage of aromatic structures (aromatic-C) found in the border samples also shows that organic matter on the border is less labile than the slower burning material in the interior of the fragments.…”
Section: Som Hf Thermal Degradabilitycontrasting
confidence: 55%
See 1 more Smart Citation
“…The lower proportion of aromatic groups in our study compared to other soils subjected to annual burning Leal et al 2019), is possibly due to the enhanced decomposition of aromatic groups by soil micribiota in the hot and humid climate of the region . The high percentage of aromatic structures (aromatic-C) found in the border samples also shows that organic matter on the border is less labile than the slower burning material in the interior of the fragments.…”
Section: Som Hf Thermal Degradabilitycontrasting
confidence: 55%
“…Although forest fragments dispersed in Amazonian savanas may have similar soils (Feitosa et al, 2016), distinctions in vegetation structure and species composition between border and interior of fragments (Santos et al 2013) can lead to diferences in the characteristcs of the organic matter pool mediated by fire intensity (Biddulph and Kellman 1998). The effects of fire on quality of SOM in forest fragments is little studied in fragments of seasonal forest dispersed in savanna matrices in the northern Brazilian Amazon (Knicker et al 2005a;Leal et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the estimated carbon mean resident times (MRTs), the control soils showed similar MRT fast values to those reported by other authors for unamended agricultural soils [38,39]. The MRT fast was significantly higher with the application of the NC at both doses-especially at a low dose, being up to 54.4 days-in contrast with AC, which did not cause any remarkable changes compared to the control.…”
Section: Degradation Of Compost Into Soc Poolssupporting
confidence: 81%
“…Amount of phosphorus and nitrate concentrations in the leachate also significantly decreased by adding each of the charcoal, sawdust and wood ash [13]. Other previous study reported that soil carbon as fulvic (10 to 20 cm) and humic acids (10 to 30 cm), and especially as humin (0 to 5 cm), increased due to increase charcoal which may be occurred by the role of the charcoal [14]. Moreover, charcoal and potassium were used to improve the growth and yield of flax plants, so from the results, the impact of both factors was clearly shown, which significantly improved the growth and productivity of flax, based on this finding do more researching on the charcoal and inorganic fertilizers on other crops are interested [15].…”
Section: Introductionmentioning
confidence: 66%